Thermal stability and heavy metal (As5+, Cu2+, Ni2+, Pb2+ and Zn2+) ions uptake of the natural zeolites from the Philippines. (15th May 2019) - Olegario, Eleanor; Pelicano, Christian Mark; Felizco, Jenichi Clairvaux; Mendoza, Herman
Abstract: Herein, we present the ability of natural zeolites from the Philippines to adsorb heavy metal (As 5+, Cu 2+, Ni 2+, Pb 2+ and Zn 2+ ) ions for the first time. The primary component of the zeolite sample is clinoptilolite based on XRD and EDX results. Surface morphological analysis revealed that the zeolite has a rough surface with layered platelet-like morphologies. Most importantly, the zeolite sample showed higher adsorption efficiencies compared with commercially available γ -Al2 O3 adsorbent. The zeolite sample also exhibited competitive maximum adsorption capacities of 125.2, 20.31, 14.65, 13.54 and 11.68 mg g −1 for Pb 2+, As 5+, Cu 2+, Zn 2+, and Ni 2+ metal ions, respectively. It also displayed selectivity (Pb 2+  > Cu 2+  ∼ Ni 2+  ∼ Zn 2+ ) for cationic heavy metal ions based on their dehydration energies. Additionally, the adsorption mechanism for As 5+ can be associated with the presence of considerable amount of Fe in the zeolite sample. Finally, the thermal analysis established that PNZ are highly stable at high temperatures. These results highlight the potential of our zeolite as a low-cost alternative for wastewater treatment and high-temperature catalyst applications.